Chemical constituents of Zizyphus sativa Gaertn fruits. Part III - Alkaloids. - Hoang Anh, Nguyen Thi; Sung, Tran Van; Arnold, Nobert; Wessjohann, L. (Vietnam Journal of Chemistry, 2014)
Two alkaloids have been isolated from Z. sativa fruits besides butane-2,3-diol and glycerol. The structures of alkaloids were established as stepharine and 1,2-dimethoxy,5,6,6a,7-tetrahydro-4H-dibenzo-quinoline by using MS, NMR spectroscopic data and by comparison with reported data.